2014
DOI: 10.1152/ajpheart.00291.2014
|View full text |Cite
|
Sign up to set email alerts
|

High-protein-low-carbohydrate diet: deleterious metabolic and cardiovascular effects depend on age

Abstract: Cottart C, Nivet-Antoine V. High-protein-low-carbohydrate diet: deleterious metabolic and cardiovascular effects depend on age. Am J Physiol Heart Circ Physiol 307: H649 -H657, 2014. First published July 11, 2014; doi:10.1152/ajpheart.00291.2014.-High-protein-lowcarbohydrate (HP-LC) diets have become widespread. Yet their deleterious consequences, especially on glucose metabolism and arteries, have already been underlined. Our previous study (2) has already shown glucose intolerance with major arterial dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
(58 reference statements)
2
22
0
1
Order By: Relevance
“…TXNIP fl/fl cdh5 cre mice and their TXNIP fl/fl littermates underwent metabolic stress induced by an HP‐LC diet. After 3 mo of an HP‐LC diet, we found that the HP‐LC‐fed TXNIP fl/fl cdh5 cre mice displayed impaired glucose tolerance similar to that previously observed with this HP‐LC diet (2). The cholesterol profile of HP‐LC‐fed TXNIP fl/fl cdh5 cre mice presented increased total cholesterol and non‐HDL cholesterol levels, associated with a shift from nonlarge to large HDL fractions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…TXNIP fl/fl cdh5 cre mice and their TXNIP fl/fl littermates underwent metabolic stress induced by an HP‐LC diet. After 3 mo of an HP‐LC diet, we found that the HP‐LC‐fed TXNIP fl/fl cdh5 cre mice displayed impaired glucose tolerance similar to that previously observed with this HP‐LC diet (2). The cholesterol profile of HP‐LC‐fed TXNIP fl/fl cdh5 cre mice presented increased total cholesterol and non‐HDL cholesterol levels, associated with a shift from nonlarge to large HDL fractions.…”
Section: Discussionsupporting
confidence: 84%
“…Dietary interventions to reduce body weight have been widely used, including low‐carbohydrate diets generally high in protein. However, they are known to have deleterious outcomes on glucose metabolism and adverse vascular effects (1, 2).…”
mentioning
confidence: 99%
“…384 The deleterious effects of high-protein/low-carbohydrate diets on the cardiovascular system appear to increase with age. 385 On the other hand, experience with the effects of a low-protein diet (0% of energy intake) on the heart is still limited only to branched-chain amino acid metabolism. 386 In short, more research is needed to delineate the effect of specific diets on both the short- and long-term function of the heart.…”
Section: Nongenetic Models For Cardiac Metabolismmentioning
confidence: 99%
“…Studies which directly examined the impact of high-fat, high-protein, low-carbohydrate diets on insulin sensitivity have reported conflicting findings, with some showing that such diets lead to glucose intolerance and insulin resistance (2)(3)(4)19), and others reporting it prevents insulin resistance (22), or causes no change in insulin resistance (5,8). While we found a steady progression of insulin-dependent Akt phosphorylation (taken as a measure of insulin effect) in hearts of animals fed CONT diet, there was an unusual response to insulin in the HFLCD-fed heart, with an initially high baseline amount of p-Akt at very low insulin levels and a blunted response as the dose was increased.…”
Section: Discussionmentioning
confidence: 99%
“…In the 13 C NMR spectrum on the right, K represents isotopomer peaks derived from ketone (3-HB); C represents those derived from carbohydrate (glucose, lactate, and pyruvate). Note that ␤-oxidation of [1][2][3][4][5][6][7][8][9][10][11][12][13] C]palmitate results in seven unlabeled acetyl-CoA fragments and one [1-ketone buffer, high insulin led to decreased FFA oxidation and upregulated ketone oxidation (P Ͻ 0.05 for high insulin compared with low insulin with the same ketone level, perfusion condition, and diet); this effect was not seen with low ketone buffer. At the low level insulin buffer, high ketone upregulated FFA oxidation and decreased ketone oxidation (P Ͻ 0.05 in the HFLCD group for high ketone compared with low ketone with the same insulin level, perfusion condition).…”
Section: Impact Of Perfusion Buffer Composition (Insulin and Ketone Lmentioning
confidence: 99%